EMPIRICAL STUDY OF FEMALE CORPORALITY INCONNECTION WITH REPRODUCTIVE FUNCTION - K. N. Belogay (Вестник Кемеровского государственного университета, 2014)
The paper discusses the results of an empirical study of female corporality (body image, body experience, physical stories) in connection with reproductive function. Corporality of mothers is compared with that of women who have no experience of gestation, childbirth and breast-feeding. The relationship between corporality and the character of the woman's pregnancy, childbirthand infant feeding period is shown.